A new index of banking coverage created from georeferenced data, with an application for Argentina (2017)
This paper constructs a Banking Index (BI) of geographic coverage and applies it to the central area of Argentina. The Index is created using georeferenced data from the first two principal components obtained applying MULTISPATI methodology, which facilitates visualization of the spatial distribution of cove- rage. Although the relative weights are similar for the partial indicators used to measure the first component of the Banking Index, some differences are detected in the weights for the second component. The BI reveals a heterogeneous level of banking coverage within the central area of Argentina.